Hemodialysis Serum Stimulates the TXNIP-eNOS-STAT3 Inflammatory Pathway In Vitro - Keren Cohen-Hagai; Hadil Kashua; Sydney Benchetrit; Tali Zitman-Gal (MDPI AG, 2023)
Background: Endothelial dysfunction, vascular inflammation and accelerated atherosclerosis have been investigated extensively in patients with chronic kidney disease (CKD). These conditions, as well as protein-energy malnutrition and oxidative stress, impair kidney function and contribute to increased morbidity and mortality among patients with end-stage kidney disease undergoing hemodialysis (HD). TXNIP, a key regulator of oxidative stress, has been linked to inflammation and suppresses eNOS activity. STAT3 activation adds to endothelial cell dysfunction, macrophage polarization, immunity and inflammation. Therefore, it is critically involved in atherosclerosis. This study evaluated the effect of sera from HD patients on the TXNIP-eNOS-STAT3 pathway using an in vitro model of human umbilical vein endothelial cells (HUVECs). Methods: Thirty HD patients with end-stage kidney disease and ten healthy volunteers were recruited. Serum samples were taken at dialysis initiation. HUVECs were treated with HD or healthy serum (10% v/v) for 24 h. Then, cells were collected for mRNA and protein analysis. Results: TXNIP mRNA and protein expression were significantly increased in HUVECs treated with HD serum compared to healthy controls (fold changes: 2.41 ± 1.84 vs. 1.41 ± 0.5 and 2.04 ± 1.16 vs. 0.92 ± 0.29, respectively), as were IL-8 mRNA (fold changes: 2.22 ± 1.09 vs. 0.98 ± 0.64) and STAT3 protein expression (fold changes: 1.31 ± 0.75 vs. 0.57 ± 0.43). The expression of eNOS mRNA and protein (fold changes: 0.64 ± 0.11 vs. 0.95 ± 0.24; 0.56 ± 0.28 vs. 4.35 ± 1.77, respectively) and that of SOCS3 and SIRT1 proteins were decreased. Patients' nutritional status, reflected by their malnutrition-inflammation scores, did not affect these inflammatory markers. Conclusions: This study showed that sera from HD patients stimulated a novel inflammatory pathway, regardless of their nutritional status.